Tranilast inhibits angiotensin II-induced myocardial fibrosis through S100A11/ transforming growth factor-β (TGF-β1)/Smad axis. Issue 1 (1st January 2021) - Chen, Youquan; Huang, Ming; Yan, Yi; He, Dequan
ABSTRACT: Tranilast has an ameliorative effect on myocardial fibrosis (MF), but the specific mechanism has not been studied. S100A11 is a key regulator of collagen expression in MF. In this paper, we will study the regulatory roles of Tranilast and S100A11 in MF. After the introduction of angiotensin II (AngII) to Human cardiac fibroblasts (HCF), Tranilast was administered. CCK-8 kit was used to detect cell viability. Wound Healing assay detected cell migration, and Western blot was used to detect the expression of migration-related proteins and proteins related to extracellular matrix synthesis. The expression of α-SMA was detected by immunofluorescence (IF). The expression of S100A11 was detected by qPCR and Western blot, and then S100A11 was overexpressed by cell transfection technology, so as to explore the mechanism by which Tranilast regulated MF. In addition, the expression of TGF-β1/Smad pathway related proteins was detected by Western blot. Tranilast inhibited Ang II–induced over-proliferation, migration and fibrosis of human cardiac fibroblasts (HCF), and simultaneously significantly decreased S100A11 expression was observed. Overexpression of S100A11 reversed the inhibition of Tranilast on AngII–induced over-proliferation, migration, and fibrosis in HCF, accompanied by activation of the TGF-β1/Smad pathway. Overall, Tranilast inhibits angiotensin II-induced myocardial fibrosis through S100A11/TGF-β1/Smad axis.